The Invasive Spider Badumna longinqua (L. Koch, 1867) (Araneae: Desidae) in Argentina: New Distributional Records, with Notes on its Expansion and Establishment - Pompozzi, Gabriel Alejandro (2013)
Badumna longinqua (L. Koch 1867) is a medium-sized spider native from Australia. Due to its synanthropic habitat, this spider expanded their range distribution, reaching Germany, Japan, New Zealand, Uruguay and USA. We found specimens of this species in different localities from Buenos Aires Province, Argentina. Therefore, we report the first records of B. longinqua to Argentina, and discuss aspects of its distribution.